Lessons from the Arctic : how Roald Amundsen won the race to the South Pole - Kløver, Geir Olav (Fram Museum, 2017)
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

Hva er en helt? Kjønn i antarktislitteraturen - Ryall, Anka (Fortid : historiestudentenes tidsskrift, UiO, 2011)
Menneskenes historie i Antarktis er ikke mer enn noen hundre år gammel. De viktigste kildene til denne historien er ekspedisjonsberetningene – en omfangsrik litteratur som kan leses på mange måter, også fra et kjønnsperspektiv.
Keywords: Antarktis; ekspedisjoner; litteratur; polarhistorie

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav; Cowlishaw, J Basil (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), a Norwegian polar explorer and national hero. The first man to find and sail through the North-West Passage, and the first to set foot on the South Pole. NORWEGIAN HERITAGE is a series of illustrated books about our most important and best-known national icons. The respective titles introduce major personalities from the worlds of art and literature, science and sports, but also the many natural wonders of the country, as well as significant historical periods and cultural expressions. Each book offers an updated introduction to readers who wish to familiarize themselves with a given subject.
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie